Immunochromatographic assay for T-2 toxin based on luminescent quantum dot beads. Issue 66 (26th November 2019) - Qie, Zhiwei; Shi, Jinmiao; Yan, Wenliang; Gao, Zichen; Meng, Wu; Xiao, Rui; Wang, Shengqi
Abstract : A quantum dot bead based immunochromatographic assay was established for T-2 toxin with a limit of detection of 0.08 ng mL −1 . Abstract : A quantum dot bead based immunochromatographic assay (QB-ICA) system was established for T-2 toxin (T-2), which widely occurs in agriculture and could be used as a potential biological warfare agent. After optimization, the dynamic linear detection range of T-2 calculated from a calibration curve was from 0.12 to 0.67 ng mL −1 and the limit of detection (LOD) was 0.08 ng mL −1, which is lower than those of the ICA based on colloidal gold nanoparticles or a fluorescent material or an antibody-based biochip in other reports. The performance and practicability of the established ICA system were validated with a commercial ELISA kit and the two methods were comparable. The proposed QB-ICA for T-2 could be an alternative for rapid, sensitive, and quantitative on-site detection of this toxin in biosafety monitoring in agriculture and for susceptibility testing of the potential release of this biological warfare agent.